FGMOS Based Voltage-Controlled Grounded Resistor - Pandey, Rishikesh; Gupta, Maneesha (Společnost pro radioelektronické inženýrství, 2010)
This paper proposes a new floating gate MOSFET (FGMOS) based voltage-controlled grounded resistor. In the proposed circuit FGMOS operating in the ohmic region is linearized by another conventional MOSFET operating in the saturation region. The major advantages of FGMOS based voltage-controlled grounded resistor (FGVCGR) are simplicity, low total harmonic distortion (THD), and low power consumption. A simple application of this FGVCGR as a tunable high-pass filter is also suggested. The proposed circuits operate at the supply voltages of +/-0.75 V. The circuits are designed and simulated using SPICE in 0.25-µm CMOS technology. The simulation results of FGVCGR demonstrate a THD of 0.28% for the input signal 0.32 Vpp at 45 kHz, and a maximum power consumption of 254 µW.
Keywords: Floating gate MOSFETs; low-voltage; voltage-controlled grounded resistor; Spice.